Góp phần nghiên cứu thành phần hóa học của cây cỏ mực (Eclipta prostrata L., Asteraceae) của Việt Nam - Giang, Phan Minh; Thơi, Nguyễn Thị; Tài, Nguyễn Văn; Sơn, Phan Tống (Vietnam Journal of Chemistry, 2015)
From the aerial parts of Eclipta prostrata L. (Asteraceae) β-sitosterol, methyl gallate, eclalbasaponin I, eclalbasaponin II, norwedelolacton, and hesperidin were isolated. Their structures were determined by using MS and NMR techniques.